5 - Gaborone is Growing like a Baby: Life Expectancies and Death Expectations in Urban Botswana - Ritsema, Mieka S. (Africa Development, 2021)
This article examines the paradox of Botswana’s twin reputations: first, success- ful national development and second, premature death from the HIV/AIDS epi- demic. While locating these reputations in the capital city, Gaborone, the article analyzes reflections of people who are themselves the audience for, and partici- pants in, the country’s development. Ethnographic data reveal a dramatic shift in discourse by generational cohort in terms of explaining the apparent contra- diction of successful development in the midst of tragedy. The article shows how official discourses of development and death are appropriated by a younger generation in Gaborone, in ways unanticipated in a meta-narrative of modernity. The emotional anguish of an older generation is absent in a younger genera- tion’s expectation that development goes hand-in-hand with funerals. The shift in perspective that is instantiated in Gaborone, reflects a profound transforma- tion in the relationship between the production of knowledge and the state’s expanding capacity since independence in 1966. This study contributes to the literature on development, modernity, African cities and the HIV/AIDS epidemic.